2010
DOI: 10.1111/j.1365-2966.2010.16689.x
|View full text |Cite
|
Sign up to set email alerts
|

Clumpy galaxies at z∼0.6: kinematics, stability and comparison with analogues at other redshifts

Abstract: Distant clumpy galaxies are thought to be Jeans‐unstable discs and an important channel for the formation of local galaxies, as suggested by recent spatially resolved kinematic observations of z∼ 2 galaxies. I study the kinematics of clumpy galaxies at z∼ 0.6 and compare their properties with those of counterparts at higher and lower redshifts. I selected a sample of 11 clumpy galaxies at z∼ 0.6 from the representative sample of emission‐line, intermediate‐mass galaxies IMAGES. Selection was based on rest‐fram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 153 publications
(339 reference statements)
4
71
0
Order By: Relevance
“…while the broad-band with HST appears photometrically irregular the objects appear kinematically regular van Starkenburg et al 2008;Puech 2010;Genzel et al 2011), a key point. Generally, the rest-frame UV and Hα from AO IFS trace each other ), whereas the stellar mass is smoother (but still clumpy) Wuyts et al 2012).…”
Section: Turbulent Disc Galaxiesmentioning
confidence: 96%
“…while the broad-band with HST appears photometrically irregular the objects appear kinematically regular van Starkenburg et al 2008;Puech 2010;Genzel et al 2011), a key point. Generally, the rest-frame UV and Hα from AO IFS trace each other ), whereas the stellar mass is smoother (but still clumpy) Wuyts et al 2012).…”
Section: Turbulent Disc Galaxiesmentioning
confidence: 96%
“…The clumpy fraction ( f clumpy ; clumpy galaxies/SF galaxies) have been investigated for different redshift and mass ranges Overzier et al 2009;Puech 2010;Guo et al 2012Guo et al , 2015Wuyts et al 2012;Murata et al 2014;Tadaki et al 2014). Despite the already mentioned differences in the clump definition, a remarkable agreement has been reached, concluding that f clumpy increases with redshift.…”
Section: Comparison With the Literature At This Redshiftmentioning
confidence: 99%
“…At intermediate redshift (z ∼ 0.6), spatially resolved kinematics has revealed that a large fraction of galaxies have chaotic velocity fields, which indicate that most local spirals have been rebuilt after a major merger since z = 1 (Hammer et al 2005;Puech 2010). At similar redshifts, Flores et al (2006) A&A 542, A54 (2012) and Yang et al (2008) investigated the velocity fields of galaxies with IFS, finding that only 35% of their sources can be classified as rotating disks while the reminder show perturbed or complex kinematics.…”
Section: Introductionmentioning
confidence: 99%